2014
DOI: 10.1002/pbc.25374
|View full text |Cite
|
Sign up to set email alerts
|

Identifying causes of variability in outcomes in children with acute lymphoblastic leukemia treated in a resource‐rich developing country

Abstract: Background The outcome of children with acute lymphoblastic leukemia (ALL) in developing countries is less favorable than in developed countries, primarily due to resource constraints. However, it is unknown whether the therapeutic results differ. Thus, we hypothesized that outcomes in resource‐rich developing countries would be similar to those in industrialized regions. Procedure We performed a retrospective analysis of 224 consecutive children with ALL, who were treated according to the Children's Cancer Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
11
1
1
Order By: Relevance
“…Although the overall frequency of prognostically relevant, common genetic lesions (RUNX1-ETV6, E2A-PBX1, BCR-ABL1, MLL rearrangements, and hyperdiploidy) in our study is different from international, regional, and national studies, it has been found to be similar to those reported from most Western, regional, and local studies 17,22,30,31 regarding its impact on patient outcome. This is evident by a significantly worse survival outcome for the HR patients (71.3%) compared with (92.4%) for SR patients at 5 years ( P  < .001).…”
Section: Discussioncontrasting
confidence: 79%
“…Although the overall frequency of prognostically relevant, common genetic lesions (RUNX1-ETV6, E2A-PBX1, BCR-ABL1, MLL rearrangements, and hyperdiploidy) in our study is different from international, regional, and national studies, it has been found to be similar to those reported from most Western, regional, and local studies 17,22,30,31 regarding its impact on patient outcome. This is evident by a significantly worse survival outcome for the HR patients (71.3%) compared with (92.4%) for SR patients at 5 years ( P  < .001).…”
Section: Discussioncontrasting
confidence: 79%
“…Patients were treated using modified regimens based on the Children's Oncology Group (COG) experience ( Table 1 ) [3] , [9] , [10] . Modifications included the use of dexamethasone instead of prednisone, and extended intensification using double delayed intensification (DI-1 and DI-2) and double interim maintenance (IM) phases.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated children with T-ALL treated before and after the substitution of high dose methotrexate (HDMTX) for standard escalating Capizzi methotrexate (C-MTX) in the first interim maintenance phase (IM1). We hypothesized that the outcomes of patients with T-ALL treated with a modified Children's Oncology Group (COG) backbone protocol [3] , [9] , [10] that included double delayed intensification and interim-maintenance (IM1 and IM2) phases while incorporating HDMTX would have superior outcomes compared to C-MTX. The effect of patient gender, age, white blood cell count (WBC), CNS involvement, testicular involvement, slow early response and treatment type on patient outcome was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…3 In the present study, SR patients were treated with CCG-1991 (regimen OD). 5 In contrast, 650 HR patients were treated on the increased intensity regimen (IPII) of the original CCG-1961 and received vincristine, prednisone, asparaginase, daunorubicin, and intrathecal methotrexate during induction and one (regimen C) or two (regimen D) delayed intensification phases. 4 In the present study, HR patients were treated on adapted CCG-1961 (regimen D) in which prednisone was replaced with dexamethasone.…”
Section: Treatment Regimenmentioning
confidence: 99%
“…4 In the present study, HR patients were treated on adapted CCG-1961 (regimen D) in which prednisone was replaced with dexamethasone. 5…”
Section: Treatment Regimenmentioning
confidence: 99%